Estudo da resistência à corrosão do aço inoxidável martensítico ASTM A743 CA-6NM - Gonçalves Filho, Gilberto Pereira (2014)
The CA-6NM A743 martensitic stainless steel has been used in services that require high mechanical strength associated to corrosion resistance, mainly in equipment’s for oil extraction, rotors and in the components of hydraulic turbines. Those equipment’s run on the acidic environment, high temperature and high mechanical resistance. The heat treatments performed in the CA-6NM A743 martensitic stainless steel are essential for obtaining the desired mechanical properties and the cycle control of heat treatments that can influence corrosion resistance. The samples were heat treated under the following conditions: austenitized for 3 hours at 1050 °C and subsequent quenched in forced air (ventilated). Afterwards, two tempers were carried out: the first tempering at 670°C for 10 hours and the second at 610°C for 15 hours. The two tempers were cooled by air. Microstructural characterization, monitoring open circuit potential, linear polarization and electrochemical impedance were performed to evaluate the corrosion resistance of the steel in different pHs. The microstructural characterization showed a martensitic microstructure and retained austenite. That residual austenite may be formed due to the low cooling rate of the molten material. In the electrochemical testing an increasingly positive interference (increase of corrosion rate) was observed for pH values below 4. For pH values between 4 and 6.5, the corrosion rate is independent of pH and relies only on the speed at which oxygen diffuses into the metal surface.